The Husband's Secret - Moriarty, Liane (London Penguin Books, 2013)
Mother of three and wife of John-Paul, Cecilia discovers an old envelope in the attic. Written in her husband's hand, it says: to be opened only in the event of my death. Curious, she opens it - and time stops. John-Paul's letter confesses to a terrible mistake which, if revealed, would wreck their family as well as the lives of others
Keywords: Letters -- Husband and wife -- Australia